Crystal structure and microwave dielectric properties of [(Mg0.6Zn0.4)0.95Co0.05]2TiO4 modified Ca0.8Sm0.4/3TiO3 ceramics. Issue 1 (January 2017) - Lin, Shih-Hung; Chen, Yuan-Bin
Abstract: High-quality x[(Mg0.6 Zn0.4 )0.95 Co0.05 ]2 TiO4 -(1-x)Ca0.8 Sm0.4/3 TiO3 ceramics were prepared by solid-state reaction. [(Mg0.6 Zn0.4 )0.95 Co0.05 ]2 TiO4 has a dielectric constant (εr ) of ~18, a high quality factor (Q×f) of ~206, 000 GHz, and a temperature coefficient of resonant frequency (τf ) of ~−20.8 ppm/°C. To produce a temperature-stable material, Ca0.8 Sm0.4/3 TiO3, which has a large positive τf value of +400 ppm/°C, was added to [(Mg0.6 Zn0.4 )0.95 Co0.05 ]2 TiO4 . 0.93[(Mg0.6 Zn0.4 )0.95 Co0.05 ]2 TiO4 −0.07 Ca0.8 Sm0.4/3 TiO3 has an excellent combination of microwave dielectric properties: εr ~18.24, Q×f ~150, 000 (at 9 GHz), and τf ~1 ppm/°C sinters at 1175 °C, and can be utilized in the fabrication of microwave devices.